2003
DOI: 10.1034/j.1600-0447.2003.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward psychiatry among students entering medical school

Abstract: Our findings suggest that psychiatry has an image problem that is widespread, reflecting community perceptions and the specialist interests of medical students on recruitment. If psychiatry is to improve its 'attractiveness' as a career option, identified image problems need to be corrected and medical student selection processes re-considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
77
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 25 publications
6
77
1
5
Order By: Relevance
“…The mean ATP-30 score of 113.9 for this group of GPs compares favourably with scores from previous studies in sixth-form students (mean ATP-30 score 110.0), 5 psychiatric residents (mean ATP-30 score 116.33) and medical students (mean ATP-30 score 103.76), 4 and with a study showing preand post-psychiatry attachment mean ATP-30 scores in medical students of 102.6 and 107.7 respectively. 12 This is reassuring, given the importance of psychiatry within the specialty, which may promote a more positive attitude among GPs than could be expected in other specialties.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…The mean ATP-30 score of 113.9 for this group of GPs compares favourably with scores from previous studies in sixth-form students (mean ATP-30 score 110.0), 5 psychiatric residents (mean ATP-30 score 116.33) and medical students (mean ATP-30 score 103.76), 4 and with a study showing preand post-psychiatry attachment mean ATP-30 scores in medical students of 102.6 and 107.7 respectively. 12 This is reassuring, given the importance of psychiatry within the specialty, which may promote a more positive attitude among GPs than could be expected in other specialties.…”
supporting
confidence: 71%
“…3 There are more recent studies regarding attitudes of medical undergraduates towards psychiatry, and these suggest unfavourable attitudes towards psychiatry as a career compared with other medical disciplines. 4 The need for proactive career advice and positive role models at an undergraduate level in order to encourage psychiatry as a career choice has been identified: 5 only 4-5% of UK graduates make this choice currently, with 10-11% being the figure needed in order to sustain recruitment requirements into psychiatry. 6 To date, undergraduate teaching in psychiatry has largely been by psychiatrists, although, with the introduction of hybrid curricula in medical schools such as that at Keele School of Medicine, 7 teaching may increasingly be provided in wider settings and by a broader group of professionals.…”
mentioning
confidence: 99%
“…According to the present study there is no statistically significant improvement in the total score of the nursing students attitudes toward psychiatric treatment and hospitals, however only three items showed significant improvement, Parikh et al (24) found that the students shows agreement about the importance of psychiatric treatment and they consider psychiatric hospitals are essential for the treatment of psychiatric ill patients, this finding contradict the finding of Malhi et al (26) who mentioned that nursing students view psychiatry as less scientific and having fewer clinically effective treatment. Sartorius et al (27) mentioned five misconception about psychotropic drugs that he thought to be the reason for the negative attitude toward psychiatric treatment, they are addictive, sedative, not curing, merely treating patients and ineffective in preventing relapse.…”
contrasting
confidence: 55%
“…A reason why male students in a traditional curriculum show a less positive attitude towards psychiatry could be seen in a widely held but wrong belief by students that this specialty is less scientific and offers fewer clinically effective treatments than other subjects (Malhi et al 2003). Since male students more often have a high school diploma focussing on sciences, they might be led by this wrong belief in rating their attitudes towards psychiatry more negatively than female students.…”
Section: Discussionmentioning
confidence: 99%
“…Attitudes of female students were more positive than those of male students (Baptista et al 1993;Kuhnigk et al 2007). (2) Number of medical school graduates who wish to specialize in psychiatry: A decrease of interest in psychiatry has been reported internationally in medical students since the 1960s from approximately 10% (Albee 1959) to currently approximately 2-5% (Ghadirian & Engelsmann 1982;Malhi et al 2003;Baboolal & Hutchinson 2007;Kuhnigk et al 2007). …”
Section: Practice Pointsmentioning
confidence: 99%